Comparable immune responsiveness but increased reactogenicity after subcutaneous versus intramuscular administration of tick borne encephalitis (TBE) vaccine. Issue 17 (12th April 2016) - Hopf, Stefan; Garner-Spitzer, Erika; Hofer, Michael; Kundi, Michael; Wiedermann, Ursula
Abstract: Evaluation of safety, immunogenicity and efficacy of vaccines during licensing studies is performed in relation to the selected vaccination route. For most adjuvanted vaccines, such as the TBE vaccine FSME-IMMUN, only intramuscular (i.m.) administration is licensed. Yet in certain situations, either because of medical indications, accidental application or due to a lack of sufficient muscular tissue, the vaccine might rather be applied subcutaneously (s.c.). With respect to the TBE vaccine there are currently however no data to support the use of the subcutaneous route of vaccination. In order to compare the reactogenicity and immune responsiveness upon i.m. and s.c. TBE vaccination 116 (58 females and 58 males) participants with a documented primary TBE vaccination course were randomized to receive either an i.m. or s.c. booster. Venous blood was collected before, 7 days, 1 month and 6 months after vaccination to determine antibody titer profiles. PBMC were isolated prior to and 7 days after booster to analyze lymphocyte subpopulations and cytokine production upon antigen restimulation. Subjects were monitored for the occurrence of side effects for 7 days post vaccination. Comparable levels of TBE specific neutralizing antibodies were induced after s.c. and i.m. vaccination. At the cellular level, IL-2, IFN gamma and IL-10 levels did not significantly differ using either route of vaccination and the distribution of T cell subsets was comparable along with a relative decrease of regulatory T-cells after both ways of administration. In contrast to the immunogenicity analyses, the data from safety diaries revealed a significantly higher rate of local, but not of systemic reactions after s.c. administration. In conclusion, this study demonstrates that both routes lead to comparable immune responses to the TBE antigen. The higher rate and intensity of local reactions, particularly among women, after s.c. vaccination however needs to be addressed during counseling.